Innovative Extraction Techniques for Maximizing Antioxidant Yield from Moringa Stenopetala Leaf: A Step Towards Sustainable Pharmaceutical Development - Fariha Kanwal; Muhammad Suleman; Syed Taimoor Ali Shah; Muhammad Ghous; Muhammad Umer; Waqas Mahmood; Saba Shairwani; Maqsood ur Rehman (Dialogue Social Science Review (DSSR), 2025)
This paper aims to uncover the processes of extraction that yield the highest antioxidant properties from Moringa stenopetala leaves due to this plant’s noteworthy bioactive compounds and sustainability opportunities. The three extraction parameters of ethanol concentration, time and pH were optimized using response surface methodology (RSM). The study established that the parameters of 50% ethanol, 66 hours, and pH 8.0 yielded the highest extractions of 67.95 ± 0.14% with phenolic content of 4.57 ± 0.02 mg GAE/mL, which was proportional to the antioxidant activity of IC50 = 0.12 ± 0.01 mg/mL. The phytochemical screening for the presence of various classes of compounds revealed alkaloids, flavonoids, phenols, tannins steroids, and terpenoids out of which flavonoids and phenols were highly richest . The study therefore confirms some of the ethnomedicinal uses and analyses the possibility of this plant as a potential source of natural antioxidants for the pharmaceutical, nutraceutical and cosmetic industries. The findings of this study highlight the need to improve extraction strategies for the enhancement of pharma development, and emphasise the significance of M. stenopetala in combating health and environmental problems across the world.